Ontology-Driven Self-Organization of Politically Engaged Social Groups - Belák, Václav; Svátek, Vojtěch, 1967 prosinec 1.-; Nováček, Vít; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2009)
This thesis deals with the use of knowledge technologies in support of self-organization of people with joint political goals. It first provides a theoretical background for a development of a social-semantic system intended to support self-organization and then it applies this background in the development of a core ontology and algorithms for support of self-organization of people. It also presents a design and implementation of a proof-of-concept social-semantic web application that has been built to test our research. The application stores all data in an RDF store and represents them using the core ontology. Descriptions of content are disambiguated using the WordNet thesaurus. Emerging politically engaged groups can establish themselves into local political initiatives, NGOs, or even new political parties. Therefore, the system may help people easily participate on solutions of issues which are influencing them.
Vedoucí práce: Vojtěch Svátek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: kognitivní informatika [obor dipl. práce]; diplomové práce; master's theses